Advances in Knowledge Management : Celebrating Twenty Years of Research and Practice - Bolisani, Ettore; Handzic, Meliha (Knowledge Management and Organizational Learning,, 2015)
This book celebrates the past, present and future of knowledge management. It brings a timely review of two decades of the accumulated history of knowledge management. By tracking its origin and conceptual development, this review contributes to the improved understanding of the field and helps to assess the unresolved questions and open issues. For practitioners, the book provides a clear evidence of value of knowledge management. Lessons learnt from implementations in business, government and civil sectors help to appreciate the field and gain useful reference points. The book also provides guidance for future research by drawing together authoritative views from people currently facing and engaging with the challenge of knowledge management, who signal a bright future for the field.